Practice does not make perfect: A brief view of athletes` knowledge on the menstrual cycle and oral contraceptives - Larsen, B.; Morris, K.; Quinn, K.; Osborne, M.; Minahan, C. (Journal of Science and Medicine in Sport, 2020)
Objectives: To assess the knowledge of Australian elite female athletes surrounding the menstrual cycle and oral contraceptives. Design: Cross sectional survey. Methods: Australian female athletes (n = 189) representing their state and/or country in their respective sport completed a questionnaire comprising questions (multiple choice and short answer) relating to the menstrual cycle and oral contraceptives. A knowledge `score` was calculated by allocating one point for each correct answer; the highest knowledge score that could be achieved was 14. Linear regression analysis was used to identify variables that were independently associated with menstrual cycle and oral contraceptive knowledge. Results: Almost half (47.1 %) of the athletes surveyed were currently using hormonal contraception, the majority (75.3 %) of which used an oral contraceptive pill. Nevertheless, the mean knowledge score achieved by athletes on the questionnaire was 5.03 ± 3.06, with only 8.5 % of athletes achieving a knowledge score of 10 or above. Hormonal contraceptive use and `identifying as an individual athlete` were two factors that were significantly associated with overall knowledge score (p = 0.004), with current hormonal contraceptive users and individual athletes scoring 1.79 and 1.66 points on average higher than non-users and team sport athletes, respectively. Conclusions: Our findings indicate that knowledge surrounding the menstrual cycle and oral contraceptives was low in most elite athletes. Further education is warranted to enable athletes to make informed decisions regarding hormonal contraception, and any educational interventions should be implemented across all athlete groups.